2016
DOI: 10.1111/bph.13513
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic NAD+ deficiency as a therapeutic target for non‐alcoholic fatty liver disease in ageing

Abstract: Hepatic concentrations of NAD + , protein levels of nicotinamide phosphoribosyltransferase (NAMPT) and several other critical enzymes regulating NAD + biosynthesis, were compared in middle-aged and aged mice or patients. The influences of NAD + decline on the steatosis and steatohepatitis were evaluated in wild-type and H247A dominant-negative, enzymically-inactive NAMPT transgenic mice (DN-NAMPT) given normal or high-fat diet (HFD). KEY RESULTSHepatic NAD + level decreased in aged mice and humans. NAMPT-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 64 publications
(99 reference statements)
10
139
2
1
Order By: Relevance
“…Our results confirmed that the ER and mitochondria were close to each other around the nucleus, and their motion was dependent on acetylated α‐tubulin and NAD+ levels in the HFD‐fed mice model. Reduction of hepatic NAD + was closely related to lipid accumulation, enhanced oxidative stress, inflammation, and impaired insulin sensitivity in the liver (11, 34). NAD + deficiency is a critical risk factor for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed that the ER and mitochondria were close to each other around the nucleus, and their motion was dependent on acetylated α‐tubulin and NAD+ levels in the HFD‐fed mice model. Reduction of hepatic NAD + was closely related to lipid accumulation, enhanced oxidative stress, inflammation, and impaired insulin sensitivity in the liver (11, 34). NAD + deficiency is a critical risk factor for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the same study, the in vitro supplementation with the NAD + -salvage metabolite NR blunted refeeding activation effect on the NLRP3 inflammasome. Interestingly, other groups have found a similar inhibitory effect of NAD + repletion by NR supplementation on hepatosteatosis, hepatic inflammation and NLRP3 inflammasome activation in mice [76, 116, 117]. Whether NR could function to suppress the NLRP3 inflammasome has the potential to be explored as a therapeutic agent, given its myriad of other beneficial effects in vivo [118121].…”
Section: Strategies and Therapeutics To Inhibit The Nlrp3 Inflammasomementioning
confidence: 97%
“…Emerging evidence supports that these proteins, and also their cofactor NAD + , are involved in metabolic diseases associated with inflammation [75, 76]. …”
Section: Sirtuins As Metabolic Sensors That Regulate Inflammationmentioning
confidence: 99%
“…The effects of NAD on a group of NAD-dependent proteins, such as the sirtuin family of proteins and PARP1, are the main mechanisms behind NAD's biological functions (Garten et al, 2015;Zhang et al, 2016;Jokinen et al, 2017). Depletion of intracellular NAD is a common pathway in many pathophysiological events, including ageing, metabolic disorders and cerebral ischaemia (Yang et al, 2002;Massudi et al, 2012;Zhang et al, 2016;Zhou et al, 2016;Wang et al, 2016a). The administration of nicotinamide mononucleotide (NMN) or nicotinamide riboside, two NAD precursors, as a supplement is able to enhance NAD levels and is used to treat high-fat-induced obesity/fatty liver (Yoshino et al, 2011;Uddin et al, 2016;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of intracellular NAD is a common pathway in many pathophysiological events, including ageing, metabolic disorders and cerebral ischaemia (Yang et al, 2002;Massudi et al, 2012;Zhang et al, 2016;Zhou et al, 2016;Wang et al, 2016a). The administration of nicotinamide mononucleotide (NMN) or nicotinamide riboside, two NAD precursors, as a supplement is able to enhance NAD levels and is used to treat high-fat-induced obesity/fatty liver (Yoshino et al, 2011;Uddin et al, 2016;Zhou et al, 2016). We and other groups have demonstrated that NMN protects against post-ischaemic NAD degradation and decreases brain damage after cerebral ischaemia Zhao et al, 2014;Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%